Unscheduled return to the operating theatre after head and neck surgery with free flap repair. Issue 5 (June 2022) - Zubair, F.; McMahon, J.; Carson, E.; McCaul, J.; Hislop, W.S.; Wales, C.; Ansell, M.; Thomson, E.; Subramaniam, S.; Fitzpatrick, K.
Abstract: The purpose of this study was to benchmark the unscheduled postoperative return to theatre rate (URTT) of patients undergoing head and neck surgery with free tissue transfer in a UK setting, and identify opportunities for quality improvement. Between August 2009 and June 2019, data on 1000 patients undergoing surgery in a single institution were prospectively assembled, and the electronic healthcare records of all patients scrutinised to obtain data on putative predictive factors. Categorical factors were analysed with the chi squared test, and continuous variables with the t test or Mann-Whitney U test, as appropriate. Multivariate logistic regression was used to identify independent predictive variables and to determine the predictive value of the final model. Of the 1000 patients 26.5% had one or more URTT, and 4.6% experienced flap failure with a 1% perioperative mortality. Failure of primary healing at the flap to mucosal interface with leakage of whole saliva into the neck wound was the single most prevalent problem (15.4%) followed by flap salvage procedures (7.4%). Independent predictive variables of URTT were perioperative transfusion, duration of procedure, requirement for tracheostomy, and previous radiotherapy to the head and neck. The C-index was weak (0.61) for this model. URTT substantially increased the duration of hospital stay. It is a poor experience for patients, and is associated with increased healthcare costs. It potentially disrupts the flow of care to other patients, and may be associated with a delay to required adjuvant therapy. Quality improvement initiatives should focus on optimising the probability of primary healing at the flap to mucosal interface, and reducing the number of flap salvage procedures.